More Similar than Different? Exploring Cultural Models of Depression among Latino Immigrants in Florida. (19th September 2011) - Martinez Tyson, Dinorah (Dina); Castañeda, Heide; Porter, Milagro; Quiroz, Marisel; Carrion, Iraida
Abstract : The Surgeon General's report, "Culture, Race, and Ethnicity: A Supplement to Mental Health, " points to the need for subgroup specific mental health research that explores the cultural variation and heterogeneity of the Latino population. Guided by cognitive anthropological theories of culture, we utilized ethnographic interviewing techniques to explore cultural models of depression among foreign-born Mexican (n = 30 ), Cuban (n = 30 ), Columbian (n = 30 ), and island-born Puerto Ricans (n = 30 ), who represent the largest Latino groups in Florida. Results indicate that Colombian, Cuban, Mexican, and Puerto Rican immigrants showed strong intragroup consensus in their models of depression causality, symptoms, and treatment. We found more agreement than disagreement among all four groups regarding core descriptions of depression, which was largely unexpected but can potentially be explained by their common immigrant experiences. Findings expand our understanding about Latino subgroup similarities and differences in their conceptualization of depression and can be used to inform the adaptation of culturally relevant interventions in order to better serve Latino immigrant communities.